A Mislocation of Double-lumen Catheter Guidewire in Right Atrium Successfully Retrieved with Loop-wire Snaring: A Case Report - Dono Antono (Acta Medica Indonesiana, 2024)
The increasing rate of central vascular access use especially for hemodialysis access in Indonesia carries risk of retention of the guidewire to the heart resulting in a condition known as heart foreign bodies. We described a case of mislocation of double-lumen catheter guidewire to the right atrium in a patient planned to perform hemodialysis. The patient complained of dyspnea and swelling of extremities but the symptoms had already appeared before the insertion of the catheter due to the patient’s underlying kidney disease arising conclusion that the foreign bodies itself are asymptomatic. The wire was found on chest x-ray and then confirmed on fluoroscopy during the retrieval procedure. Loop-wire was used to snare the guidewire. The wire was successfully evacuated and the patient was stable. The rare nature of the condition could become a challenge in recognizing the condition. Percutaneous retrieval is the preferred management of the condition.